(untitled) (Journal of Engineering, 2009)
The present study investigates the removal of the textile dyehouse wastewater [azo dye para red(reactive dye)and M-5R200%(disperse oranges dye)] by Electrocaogulation process. The effect of nature of the anode, current density, initial pH, rate of stirring and concentration of dyes on the removal efficiency were tested. The experimental results showed that the color of dyes in the aqueous solution was effectively removed when aluminum was used as anodes and the current density 25mA/cm2 , initial pH (3-9),stirring rate 200rpm, and the concentration of dyes was less than 100mg/l. When the concentration of reactive dye exceeded 300mg/l iron was a more suitable anode than aluminum. For the electrocaogulation of disperse dye in aqueous solution aluminum as anode was more suitable than iron when the concentration exceeded 300mg/l. The removal efficiency of reactive dye was increased to 90% when using iron as anode and the removal efficiency of disperse dye 96% when aluminum was used as anode at different running time (10-30) minute.